24 | Intervention “The Mediterranean Diet Game”: promotion of healthy eating in schools of the Local Health Authority “Napoli 3 Sud” - M. Matarese; A. Antignani; R. Balzano; L. Battiloro; F. Bisesti; A. Dato; M. Di Costanzo; O. Di Geronimo; S. Forte; E. Galeota Lanza; S. Mantovano; T. Mastantuono; et al. (Journal of Biological Research - Bollettino della Società Italiana di Biologia Sperimentale, 2026)
Background. The Food and Nutrition Hygiene Service of Local Health Authority “Napoli 3 Sud” developed The Mediterranean Diet Game (Med-Game), as part of the “Health Promoting SHE School Regional Network” – PRP Campania 2020-2025, a Mediterranean diet-inspired intervention to promote healthy eating and physical activity from the 2022/2023 school years. The Med-Game, dedicated to students belonging to the Primary School, is an educational play consisting of eight thematic units to learn foods of the Mediterranean Diet, such as fruits and vegetables, cereals, milk and dairy products, legumes, fish, meat, eggs and virgin olive oil. The goal was to involve students, their families and teachers to increase their health literacy and empowerment. Materials and Methods. The intervention was implemented in schools of the ASL Napoli 3 Sud area from the 2022/2023 to the 2025/2026 school years. 2-hour training courses were performed to teachers and parents to improve their health literacy skills and to explain the Med-Game activities. Results. The schools adhering to the Med-Game were 67 ± 2.08 in each school years from the 2022/2023 to the 2025/2026, involving approximately 10.000 students in each school years. An increased number of teachers participating to the training course were observed (979 vs. 950; school years 2025/2026 vs. 2022/2023) as well as parents (374 vs. 270; school years 2025/2026 vs. 2022/2023) from the 2022/2023 to the 2025/2026. Conclusions. In the 4 school years a growing number of teachers and parents were involved. According to several studies, school and family environment play an important role in promoting healthy lifestyle behaviours. Therefore, the involvement of teachers and parents represents a key step to modify eating habits in children.